Acute effects of capacitive and resistive electric transfer (CRet) on the Achilles tendon. (2nd January 2019) - Bito, Tsubasa; Tashiro, Yuto; Suzuki, Yusuke; Kajiwara, Yuu; Zeidan, Hala; Kawagoe, Mirei; Sonoda, Takuya; Nakayama, Yasuaki; Yokota, Yuki; Shimoura, Kanako; Tatsumi, Masataka; Nakai, Kengo; et al.
ABSTRACT: This study aimed to investigate the acute effects of capacitive and resistive electric transfer (CRet) on Achilles tendon elongation during muscle contraction, as well as the circulation in the peritendinous region. Sixteen healthy men participated in this study. All 16 participants underwent 2 interventions: (1) CRet trial and (2) CRet without power (sham trial). Tendon elongation was measured four times. Using near-infrared spectroscopy, the blood circulation (volume of total-hemoglobin (Hb), oxygenated hemoglobin (oxy-Hb), and deoxygenated hemoglobin (deoxy-Hb)) was measured for 5 min before the intervention and for 30 min after the intervention. The differences between the measurements obtained before and after intervention were compared between the two interventions. The changes in tendon elongation and deoxy-Hb were not significantly different between the interventions. Total- and oxy-Hb were significantly increased in the CRet trial compared with the sham trial. In addition, the increases in total-Hb and oxy-Hb lasted for 30 min after the CRet intervention (CRet vs. sham: oxy-Hb: F = 8.063, p = 0.001, total-Hb: F = 4.564, p = 0.011). In conclusion, CRet significantly improved blood circulation in the peritendinous region.